Combination of long-acting microcapsules of the D-tryptophan-6 analog of luteinizing hormone-releasing hormone with chemotherapy: investigation in the rat prostate cancer model. - Schally, A V (1985)
The effect of combining hormonal treatment consisting of long-acting microcapsules of the agonist [D-Trp6]LH-RH (the D-tryptophan-6 analog of luteinizing hormone-releasing hormone) with the chemotherapeutic agent cyclophosphamide was investigated in the Dunning R-3327H rat prostate cancer model. Microcapsules of [D-Trp6]LH-RH formulated from poly(DL-lactide-co-glycolide) and calculated to release a controlled dose of 25 micrograms/day were injected intramuscularly once a month. Cyclophosphamide (Cytoxan) (5 mg/kg of body weight) was injected intraperitoneally twice a week. When the therapy was started 90 days after tumor transplantation--at the time that the cancers were well developed-and was continued for 2 months, tumor volume was significantly reduced by the microcapsules or Cytoxan given alone. The combination of these two agents similarly inhibited tumor growth but did not show a synergistic effect. In another study, the treatment was started 2 months after transplantation, when the developing tumors measured 60-70 mm3. Throughout the treatment period of 100 days, the microcapsules of [D-Trp6]LH-RH reduced tumor volume more than Cytoxan did, and the combination of the two drugs appeared to completely arrest tumor growth. Tumor weights also were diminished significantly in all experimental groups, the decrease in weight being smaller in the Cytoxan-treated group than in rats that received the microcapsules. The combination of Cytoxan plus the microcapsules was 10-100 times more effective than the single agents in reducing tumor weights. In both experiments, testes and ventral prostate weights were significantly diminished, serum testosterone was suppressed to undetectable levels, and prolactin values were reduced by administration of microcapsules of [D-Trp6]LH-RH alone or in combination with Cytoxan. These results in rats suggest that combined administration of long acting microcapsules of [D-Trp6]LH-RH with a chemotherapeutic agent, started soon after the diagnosis of prostate cancer is made, might inhibit the proliferation of androgen-dependent and -independent cells, improve further the therapeutic response, and increase the survival rate.